Fungal conversion of chicken-feather waste into biofortified compost - S. Masood (Brazilian Journal of Biology, 2022)
Abstract Poultry industry is amongst highly developed industries of Pakistan, fulfilling the protein demand of rapidly increasing population. On the other hand, the untreated poultry waste is causing several health and environmental problems. The current study was designed to check the potential of keratinolytic fungal species for the conversion of chicken-feather waste into biofortified compost. For the purpose, three fungal species were isolated from soil samples. These strains were pure cultured and then characterized phenotypically and genotypically. BLAST searches of 18S rDNA nucleotide sequence of the fungal isolates revealed that the two fungal isolates belonged to genus Aspergillus and one belonged to genus Chrysosporium. Optimum temperature for Aspergillus flavus, Aspergillus niger and Chrysosporium queenslandicum was 29, 26 and 25 oC, respectively. A. flavus showed maximum (53%) feather degradation, A. niger degraded feather waste up to 37%, while C. queenslandicum showed 21% keratinolytic activity on chicken feathers at their respective temperature optima. The degradation potential of these fungal species showed their ability to form compost that has agro-industrial importance.